Acute effects of commercial energy drink consumption on exercise performance and cardiovascular safety: a randomized, double-blind, placebo-controlled, crossover trial - Nile F. Banks; Emily M. Rogers; Nate J. Helwig; Laura E. Schwager; Justin P. Alpers; Sydni L. Schulte; Emma R. Trachta; Christopher M. Lockwood; Nathaniel D.M. Jenkins (Journal of the International Society of Sports Nutrition)
The aim of this study was to examine the acute effects of a non-caloric energy drink (C4E) compared to a traditional sugar-containing energy drink (MED) and non-caloric placebo (PLA) on exercise performance and cardiovascular safety. Thirty healthy, physically active males (25 ± 4 y) completed three experimental visits under semi-fasted conditions (5–10 h) and in randomized order, during which they consumed C4E, MED, or PLA matched for volume, appearance, taste, and mouthfeel. One hour after drink consumption, participants completed a maximal, graded exercise test (GXT) with measurement of pulmonary gases, an isometric leg extension fatigue test (ISOFTG), and had their cardiac electrical activity (ECG), leg blood flow (LBF), and blood pressure (BP) measured throughout the visit. Neither MED nor C4E had an ergogenic effect on maximal oxygen consumption, time to exhaustion, or peak power during the GXT (p > 0.05). Compared to PLA, MED reduced fat oxidation (respiratory exchange ratio (RER) +0.030 ± 0.01; p = 0.026) during the GXT and did not influence ISOFTG performance. Compared to PLA, C4E did not alter RER (p = 0.94) and improved impulse during the ISOFTG (+0.658 ± 0.25 V·s; p = 0.032). Relative to MED, C4E did not significantly improve gas exchange threshold (p = 0.05–0.07). Both MED and C4E increased systolic BP at rest (+7.1 ± 1.2 mmHg; p < 0.001 and + 5.7 ± 1.0 mmHg; p < 0.001, respectively), C4E increased SBP post-GXT (+13.3 ± 3.8 mmHg; p < 0.001), and MED increased SBP during recovery (+3.2 ± 1.1 mmHg; p < 0.001). Neither MED nor C4E influenced ECG measures (p ≥ 0.08) or LBF (p = 0.37) compared to PLA. C4E may be more efficacious for improving performance in resistance-type tasks without altering fat oxidation under semi-fasted conditions during fatiguing exercise bouts, but promotes similar changes in BP and HR to MED.